"STUDIES ON THE INTESTINAL PARASITES IN CHILDREN OF TEHRAN NURSERY SCHOOLS" - M.Bahmanrokh; M. Mahmoodi; J. Masood (Tehran University of Medical Sciences, 1992)
One thousand children from 20 day care centers were studied for intestinal parasites in Tehran. The stool samples Collected from 0 - 6.6 years old Children and examined by formalin ether concentration method for parasitic ova and cyst. Cellophane tape technique (Graham's method) also applied for Enterobius vermicularis diagnosis, of these 454 children were positive. E.vermicularis with the rate of 272 per thousand)Giardia lamblia (204) per thousand) and Entamoeba Coli (55 per thousand)were the Commonest parasites found. The prevalence rate of other parasites present included Hymenolepis nana (13); E. histolytica (9); Ascaris lumbricoides (7); E. hartmanii, Endolimax nana (5); Dientamoeba fragilis (6); lodamoeba butchelii, Chi1omastix meseneli (3); and Trichurjs trichiura, Trichomonas hominis (1) per thousand. There were no difference in.the rate of infections between boys and girls with exception for E. histolytica. The significantly higher precvalence rate of E. vermicularis was found in age group of 4-6 years. There was no difference between various age groups of other parasites.